Correlation of VO2max and Agility with Futsal Playing Skills - Jud, Jud; Rusli, Muhammad; Marsuna, Marsuna (Performa, 2023)
A low VO2max can slow down the recovery process, which can affect skills in subsequent matches. When athletes become tired, their agility and technical skills decline. Low VO2max ability and limited agility can also affect athletes' psychology in futsal playing skills. The aim of this research is to determine the correlation between VO2max and agility with futsal playing skills. The method used is quantitative research with a correlational design. The population in this study was 30 students who took part in extracurricular activities at SMA 2 Kendari. The sampling technique used total sampling, namely the entire population sampled was 30 people. The VO2max test instrument uses the Cooper test. Agility instruments use agility tests. The instrument for playing futsal skills uses passing, controlling and shooting tests. Based on the results of the correlation test between VO2max, agility and futsal playing skills (rx1x2Y) which is 0.758 with a significance value of 0.000 with a coefficient of determination of 0.57 or 57% supported by the VO2max and agility factors, it can be concluded that there is a correlation between VO2max and agility and playing skills. futsal with a significance value <0.05. From the research results it can be concluded that there is a significant correlation between VO2max and agility with futsal playing skills.